(untitled) (Asian Journal of Social Science Studies, 2018)
Investigation of the impact multimedia-based off-line learning towards student motivation and outcomes was carried out based on ADDIE model, and the 2013 vocational high school curriculum content standards. It was found that the implementation of the multimedia was highly usefull as a learning device. The population of this study were students of grade XI of a vocational high school 1 in Percut Sei Tuan, Medan Indonesia. The sample selected was 2 classes of the grade XI and classified into experimental and controlled groups which consisted of 36 students respectively. The experimental group was taught by the MAOL and the controlled group taught by web-based adobe flash-based instruction (WAFI) learning approaches. Instruments used to collect data student motivation and outcomes were questionnaires and achievement tests respectively. The Data collected were analyzed with SPSS softwares. The results showed that the student motivation and achievements of the experimental group were significantly higher than the controlled group on the subject of acid and base solutions, with a significance level of 5% (with the criteria of Sig <α value is 0.001 < 0.05) ; Furthermore, there was a positive correlation between motivation and student outcomes at a significance level of 5%.